Review Paper on Different Dual Band Printed Slot Antenna for 5G Wireless Communication - Vibha Raj Nag; Mrinal Sarvagya (International Journal of Informatics and Communication Technology (IJ-ICT), 2018)
With advancement in communication technology over the past decade, there is an increasing demand for miniaturization, cost effective, multiband and wideband antennas. Dual band printed slot antenna designs can support in meeting these requirements. Various techniques, different shapes and geometries have been introduced for size reduction of dual band printed slot antennas. This paper is on various techniques for designing dual band printed slot antenna exhibits details of different geometries developed to get multiband behavior of printed slot antenna. In this paper geometry of the antenna and variousparameters such as return loss plot, gain plot, radiation pattern plot and VSWR plot are discussed. In this paper the review on various techniques of compactness by geometry on different shapes of printed slot antenna for 5G next generation wireless (NGW) mobile application are presented